URGENSI PENDIDIKAN NILAI UNTUK ACEH DAMAI BERKELANJUTAN - M. Jamil Yusuf (Islam Futura, 2011)
Sustainable peace in Aceh should be started from the critical value of education and education based values are integrated in all subjects and can be taught at each level of development. The assumption is that the value of education is needed at each level of development and need to be implemented on all aspects of life. The Education curriculum should reflect the religious values, independence and entrepreneurship as cores value of education, as well as the values of excellence (excellence) that should be achieved by everyone at all levels and types of education in its path. Both of these values must be built through the education system that is able to develop a good understanding, the courage to think, to act and be able to build the establishment of persistence. Educational value may be applied only in a democratic educational system, in which the learner to express his opinions in an atmosphere of mutual understanding. Learners need to be portrayed as subjects with individual excellence, which is reflected in the ability to build friendship, cooperation within the group, achieve higher performance, empathize with others, able to solve problems, resolve conflicts, have a sense of humor, self-motivated when faced with periods of tough and able to face tough times with confidence. With this advantage, they feel proud of their education and meaningful to the advancement of his career. As such, they have a place in the field of work and the opportunity of participation in any development process and not feel marginalized.